1998
DOI: 10.1111/j.1558-5646.1998.tb01658.x
|View full text |Cite
|
Sign up to set email alerts
|

The Maintenance of Sex by Parasitism and Mutation Accumulation Under Epistatic Fitness Functions

Abstract: The mutation accumulation hypothesis predicts that sex functions to reduce the population mutational load, while the Red Queen hypothesis holds that sex is adaptive as a defense against coevolving pathogens. We used computer simulations to examine the combined and separate effects of selection against deleterious mutations and host-parasite coevolution on the spread of a clone into an outcrossing sexual population. The results suggest that the two processes operating simultaneously may select for sex independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
85
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 30 publications
3
85
1
Order By: Relevance
“…Specifically, Howard and Lively (1994), and others since (Howard and Lively 1998;Park et al 2010), investigated the competitive ability of sexual vs. asexual populations of hosts in the presence of coevolving parasites and deleterious mutations. By focusing on the asexuals, we can compare their model with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Howard and Lively (1994), and others since (Howard and Lively 1998;Park et al 2010), investigated the competitive ability of sexual vs. asexual populations of hosts in the presence of coevolving parasites and deleterious mutations. By focusing on the asexuals, we can compare their model with ours.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the rate of mutation per genome has not been studied in psychid moths, most asexual populations are quite small (see Materials and Methods) and hence the conditions could also be suitable for Muller's ratchet (Muller 1964) to work. However, West et al (1999) emphasized the importance of a pluralistic view instead of finding simple explanations for the maintenance of sex in complex systems, and Howard and Lively (1998) suggested that even moderate effects of parasites together with mutation accumulation could act in favor of sex. However, in our study system it is unlikely that mutation accumulation could explain the maintenance of sexuals as the life-history measurements do not indicate any phenotypic abnormalities among the asexuals.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical studies have often focused on the success of sexuals versus asexuals (e.g., Rispe and Pierre 1998;Doncaster et al 2000;Peck and Waxman 2000), but the actual paradox of the maintenance of sex still remains. Apart from the outstanding studies on New Zealand freshwater snails (Lively 1992;Fox et al 1996;Jokela et al 1997;Howard and Lively 1998), there is very little empirical data from natural systems where sexually and asexually reproducing morphs of nonhybrid origin coexist and compete with each other (snail, Campeloma limum: Johnson 2000; flatworm, Schmidtea polychroa: Michiels et al 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Jaenike 1977;Hamilton 1980;Hamilton et al 1990;Howard & Lively 1998). Two previous studies have contrasted selffertilization ('selfing') and outcrossing, both of which are forms of sexual reproduction.…”
Section: Introductionmentioning
confidence: 99%